PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP SIKAP RELIGIUS PESERTA DIDIK DALAM PEMBELAJARAN PAI DI SMA NEGERI 1 LIMBOTO: Pengaruh Kecerdasan Spiritual dan Kecerdasan Emosional terhadap Sikap Keagamaan Siswa di Kelas Pendidikan Agama Islam di SMA Negeri Limboto 1 - Zakaria, Alfian; Mohamad Shabri Hatlah; Posangi, Posangi; Arif, Arif; Said Subhan, Said Subhan; Muh., Muh. (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC UNIVERSITY, 2026)
Instilling religious attitudes is one of the main objectives of Islamic Religious Education (IRE), but in practice, students' religious understanding is often still cognitive in nature and has not been fully internalized in their daily attitudes and behavior. This condition underscores the importance of attending to students' internal factors, particularly spiritual and emotional intelligence, in the learning process. This study aims to analyze the influence of spiritual intelligence and emotional intelligence on students' religious attitudes in Islamic Religious Education. This study uses a quantitative, correlational design. The study population consisted of 986 students at Limboto 1 Public High School, and a sample of 284 students was selected using the Slovin formula via proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression after satisfying the classical assumption tests. The results showed that spiritual intelligence and emotional intelligence had a positive and significant effect on religious attitudes, both partially and simultaneously. Spiritual intelligence had a more dominant effect than emotional intelligence. The coefficient of determination (R²) value of 0.669 indicates that these two variables can explain 66.9% of the variation in religious attitudes. This study concludes that strengthening spiritual and emotional intelligence is an important factor in shaping students' religious attitudes and should therefore be systematically integrated into Islamic Education (PAI) learning.